Morphology and thickness of the buccal bone wall of the maxillary central incisors in population: a CBCT study - Song, Yaping; Yang, Song; Wang, Chao (Frontiers in Dental Medicine, 2024)
The objective of this study was to measure and analyze the anatomical morphology and thickness of the buccal bone wall (BBW) of the maxillary central incisors, providing a theoretical basis for immediate implant surgery. A total of 372 maxillary central incisors were collected and classified into B and P types based on the root position and the degree of coverage of the BBW. The cases were divided into male and female groups, with 180 males and 192 females. The thickness of the BBW was measured at three measurement locations: 4 mm apical to the cementoenamel junction (CEJ), the mid-root, and the root apex. The number and proportion of various types of BBW are as follows: B1 (54, 14.52%), B2 (72, 19.35%), B3 (61, 16.40%), P1 (76, 20.43%), P2 (66, 17.74%), and P3 (43, 11.56%). In the B type group, the thickest BBW at 4 mm apical to the CEJ and the mid-root was observed in B3 (0.89 mm ± 0.09 mm, 0.56 mm ± 0.07 mm). The thickest BBW at the root apex was observed in B2 (0.46 mm ± 0.05 mm). In the P-type group, the thickest BBW at all three measurement locations was observed in P3 (1.10 mm ± 0.08 mm, 1.04 mm ± 0.11 mm, 3.59 mm ± 0.12 mm). The BBW of the maxillary central incisors in males was thicker than that in females. The conclusion drawn was that most BBW of the maxillary central incisors are thin, with a portion of the maxillary central incisors having only a thin BBW coverage at 4 mm apical to the CEJ and no significant bone wall coverage elsewhere. This Type of maxillary central incisor presents a higher risk of buccal soft and hard tissue recession and even bone fenestration after implant surgery. It is, therefore, crucial to assess the three-dimensional position of the root and measure the thickness of the BBW using Cone-beam computed tomography (CBCT).